Development of a behavioural assessment system for achievement motivation in soccer matches - Shafizadeh, M.; Gray, S. (Journal of Quantitative Analysis in Sports, 2011)
The aim of present investigation was to develop the behavioural instrument for measuring the achievement motivation in sport matches. According to 5-stage behavioural measurement system, the instrument was established and was applied for Iran national soccer team among three matches. The results have revealed the good validity, intra-rater, and inter-rater reliabilities for measuring motivational behaviours in sport contexts. In addition, the repeated measure analysis of variance has shown the applicability of new instrument for studying the association of achievement behaviours with successful performance, through significant differences between achievement behaviours in different matches with varied outcomes (p<.05).It seems the developed instrument is applicable for coaches to discriminate achievement behaviours of players during the match and select their strategy and players` substitutions according to their trends and behaviours for success.